Deriving Competencies for Mentors of Clinical and Translational Scholars - Abedin, Zainab (Blackwell Publishing Inc, 2012)
Although the importance of research mentorship has been well established, the role of mentors of junior clinical and translational science investigators is not clearly defined. The authors attempt to derive a list of actionable competencies for mentors from a series of complementary methods. We examined focus groups, the literature, competencies derived for clinical and translational scholars, mentor training curricula, mentor evaluation forms and finally conducted an expert panel process in order to compose this list. These efforts resulted in a set of competencies that include generic competencies expected of all mentors, competencies specific to scientists, and competencies that are clinical and translational research specific. They are divided into six thematic areas: (1) Communication and managing the relationship, (2) Psychosocial support, (3) Career and professional development, (4) Professional enculturation and scientific integrity, (5) Research development, and (6) Clinical and translational investigator development. For each thematic area, we have listed associated competencies, 19 in total. For each competency, we list examples that are actionable and measurable. Although a comprehensive approach was used to derive this list of competencies, further work will be required to parse out how to apply and adapt them, as well future research directions and evaluation processes. Clin Trans Sci 2012; Volume 5: 273–280